INDIAN CLASSICAL MUSIC AS RECEPTIVE MUSIC THERAPY IMPROVES TRIDOSHIC BALANCE AND MAJOR DEPRESSION IN A PREGNANT WOMAN - Sumathy, *Sundar; Pavitra, Durai; Parin N, Parmar (International Journal of Ayurveda and Pharma Research, 2016)
It is known that music therapy is effective in various psychiatric disorders, but not much research has been done to assess effect of Indian classical music on psychiatric disorders. We report a 27-year-old pregnant female suffering from major depression for 3 years who was treated with receptive music therapy using Indian classical music. The selection of Raga (a specific melodic structure and pattern used in Indian classical music which has to be followed strictly) for her music therapy was based on her Tridoshic analysis as per Ayurveda and on Time Theory of Ragas. She was treated with 20 sessions of receptive music therapy; frequency of the sessions being 3 sessions per week. She was evaluated using Carroll Rating Scale for Depression and Tridosha evaluation before starting music therapy, after 10 sessions, and after 20 sessions of music therapy. At end of 20 sessions of music therapy, improvement was seen in all symptoms of depression and Carroll Rating Scale for Depression showed progressive improvement (pre-treatment score: 16, after 10 sessions: 11, after 20 sessions: 5). Her Tridosha evaluation also showed progressive changes towards improved balance between the Doshas (pre-treatment: Vata - 7, Pitta - 16, Kapha - 3; after 10 sessions: Vata - 9, Pitta - 14, Kapha - 6; after 20 sessions: Vata - 12, Pitta - 14, Kapha - 10). Further scientific studies are required to evaluate the concepts of Time Theory of Ragas, effect of Indian classical music on body physiology and psychology in both healthy and diseases states, and effect of music therapy on the Tridoshas.